Evaluation of endometriosis risk factors, symptoms, and clinical treatments in Bangladesh: a cross-sectional study - Afrose, Afsana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2024.